Pengaruh Pengelolaan Fasilitas Umum Terhadap Minat Kunjungan Wisatawan Objek Wisata Air Terjun Guruh Gemurai di Desa Kasang Kecamatan Kuantan Mudik Kabupaten Kuantan Provinsi Riau - Nona Masni Boru Manalu; Rusmauli Simbolon; Mery Silalahi; Robert Juni Tua Sitio; Maringan Sinambela (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to determine the influence of public facilities on tourist interest in visiting the Guruh Gemurai Waterfall tourist attraction in Kasang Village, Kuantan Mudik District, Kuantan Singingi Regency, Riau Province. The method used in this research uses descriptive quantitative methods. The population is all tourists who visit the Guruh Gemurai Waterfall tourist attraction and the total average number of tourists in January-June 2023 is 100 tourists and the sample is set at 30 people. Data was collected using positive closed items totaling 22 items, namely 12 items for variable Riau Province: 1) Test analysis requirements: a) positive relationship test obtained by the value rxy = 0.461 > rtable(α=0.05,n=30) = 0.361, thus it is known that there is a positive relationship between variable X and variable Y. b) Testing a significant relationship obtained a value of tcount= 2.746 > ttable(α=0.05,dk=n-2=28)= 2.048, thus there is a significant relationship between variable X and variable Y. c) Test the regression coefficient of determination ( r2) = 21.2%. 2) Influence test: Regression equation test, obtained regression equation. Thus Ha is accepted and H0 is rejected.